Retinopathy and optic neuropathy following closantel treatment of ewes. Issue 1 (5th March 2014) - Crilly, James Patrick; del Pozo, Jorge; Scott, Philip R; Wilson, David J; Sargison, Neil D; Truyers, Isabelle
Abstract : An outbreak of sudden onset blindness subsequent to dosing with oral closantel affecting 1 per cent of a six hundred ewe flock was investigated. Clinical examination and histopathology both revealed features fully consistent with closantel toxicity despite the maximum dose received by the affected sheep not exceeding 14.5 mg/kg (recommended dose rate 10 mg/kg). The interval between dosing and the onset of clinical signs had been recorded accurately (minimum interval eight days) and was found to be longer than in previous reports.